Kegiatan Mahasiswa KKN di Desa Bipak Kali dalam Membangun Generasi Cerdas Melalui Literasi Membaca dengan Inisiatif Bersama Karang Taruna Kecamatan Gunung Bintang Awai Kabupaten Barito Selatan - Elisa Saputri; Yamowa’A Bate’E; Lexi Elang Taruna R. Aden; Jhonatan Jhonatan; Sonar Womswor; Sela M; Andreas Vicky Anugrahno Pansla; Lola Saputri; Aning Kristiani; Yuni Esa Gresella; Yusnani Yusnani; Mitae Mitae; Kristina Kristina; Runia Mustika; Tira Watie; Sri Anjini; Handriani JH (Kolaborasi : Jurnal Hasil Kegiatan Kolaborasi Pengabdian Masyarakat, 2024)
This research aims to improve reading literacy among children in Bipak Kali Village through collaboration between KKN students and Karang Taruna. This program focuses on increasing reading interest, reading ability, and access to literacy resources. A mixed-method approach was used in this study, which involved surveys, interviews, participatory observations, and group discussions. The work program carried out includes literacy socialization, the formation of study groups, and other supporting activities. The evaluation was carried out to measure the effectiveness and impact of the program. The results of the study showed a significant increase in reading interest, reading ability, and access to literacy resources among children in Bipak Kali Village. Community participation has also increased, and the program has received support from various parties, including the Youth Organization, the village government, and community leaders. Program evaluations identify several challenges and provide recommendations for the development of more effective and sustainable literacy programs.